On the Origins and Development of Pakistan’s Soccer-Ball Cluster - Atkin, David; Chaudhry, Azam; Chaudry, Shamyla; Khandelwal, Amit K.; Raza, Tariq; Verhoogen, Eric (Published by Oxford University Press on behalf of the World Bank, 2019)
Sialkot, Pakistan, is the world center of hand-stitched soccer-ball manufacturing. The existence of the cluster is puzzling and seems to argue against the “home market effect”, since there is little local demand for soccer balls. This paper traces the development of the cluster from its origins in the late 1800s and shows that it was rooted in an initial home market effect due to the presence of British colonists. Subsequent expansion was driven by agglomeration forces and effective industrial policy. The case study underlines the importance of longer-term historical dynamics and the role of industrial policy for understanding a country’s contemporaneous pattern of specialization in the world economy.